Interpersonal communication of midwives to reduce maternal and neonatal mortality in Indonesia - Siti Nursanti,; Yanti Tayo,; Wahyu Utamidewi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The high incidence of maternal and neonatal mortality is a burden for governments globally, considering maternal and neonatal mortality are indicators of a nation's health. Various efforts have been attempted to reduce maternal and neonatal mortality, including reproductive health literacy, screening programs for pregnant women, improved pregnancy nutrition, and increased health professional accountability. This research aimed to establish the level of interpersonal communication ability required by midwives, pregnant women, and their families. A qualitative research approach with a case study method was used. This research involved six informants from three groups: program creators, program implementers, and program recipients. This research demonstrated that each communicator must enhance communication competency, such as effective listening, maintaining secrets, opening up, and empathizing, to establish successful interpersonal communication between midwives, pregnant women, and mothers' families. Empathy is essential for effective communication between midwives, expectant mothers, and their families. The intended empathy occurs when communicators have a mutual understanding of each other's positions and do not impose their will on each other, creating the impression that the other party is ignoring them. Efforts to save mothers and neonatal are a responsibility that must be carried out by all parties; this is not only the responsibility of the government, midwives, or mothers of neonatal, but collaboration that is carried out collaboratively is required so that efforts to save mothers and neonatal can have a positive impact and bring about significant change with shared benefits.